2021
DOI: 10.3390/foods10112661
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Chilling of Whitefish: Effects of Capture, On-Board Processing, Freezing, Frozen Storage, Thawing, and Subsequent Chilled Storage—A Review

Abstract: The current review investigates how whitefish quality is affected by capture at sea, on board handling, freezing, double freezing, frozen storage, thawing, and chilled storage. Packaging of fillets in MAP and vacuum are also covered. The main goal was to evaluate the freeze-chilling concept as a possible method for the fishing industry for all-year-round marketing of fish captured during the relatively short fishing period. The review covers both the effect of each processing step in the supply chain as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…Marginal mean hemoglobin concentration was significantly higher in fillets from fish bled 40 min after catch (0.147 mg Hb/g muscle) than in fillets from fish bled immediately (0 min) after catch (0.137 mg Hb/g muscle) (p < .001). These findings are in accordance with previous studies as reviewed by Erikson et al (2021), which showed that postponed bleeding negatively affected the quality of the fish. The effects of other factors on the blood drainage of fish, such as slaughter and cutting method (Digre et al 2011;Olsen et al 2006;Roth et al 2005), temperature (Olsen et al 2006), and water flow (Eliasson et al 2020), have also been investigated.…”
Section: Effect Of Bleeding Time On Hemoglobin Concentration In Cod F...supporting
confidence: 93%
“…Marginal mean hemoglobin concentration was significantly higher in fillets from fish bled 40 min after catch (0.147 mg Hb/g muscle) than in fillets from fish bled immediately (0 min) after catch (0.137 mg Hb/g muscle) (p < .001). These findings are in accordance with previous studies as reviewed by Erikson et al (2021), which showed that postponed bleeding negatively affected the quality of the fish. The effects of other factors on the blood drainage of fish, such as slaughter and cutting method (Digre et al 2011;Olsen et al 2006;Roth et al 2005), temperature (Olsen et al 2006), and water flow (Eliasson et al 2020), have also been investigated.…”
Section: Effect Of Bleeding Time On Hemoglobin Concentration In Cod F...supporting
confidence: 93%
“…For example, Olsen et al 72 reported that cod should be bled immediately after capture, no later than 30–60 min post‐mortem 73 . A short bleeding duration (5 min) is sufficient for proper drainage of blood 74 . In the pilot projects, Mraz et al, 53 studied the effect of different bleeding methods on the quality of common carp.…”
Section: Slaughtering Methods and Farm‐to‐fork Lossesmentioning
confidence: 99%
“…73 A short bleeding duration (5 min) is sufficient for proper drainage of blood. 74 In the pilot projects, Mraz et al, 53 studied the effect of different bleeding methods on the quality of common carp. Results suggested that bleeding time must be within 30 min of stunning considered to avoid fish spoilage in the subsequent steps.…”
Section: Bleeding Filleting and Cleaningmentioning
confidence: 99%
“…However, prepared foods are not easy to preserve [153], and most of them require cold-chain transportation to each sales location. In the process of processing, preservation, distribution, and consumption, prepared foods need to go through the process of bumping, kneading, chilling/freezing, and then thawing and reheating [154]. After these processes, their sensory qualities, such as colour, flavour, taste, and appearance, will be affected [62].…”
Section: Loss Of Nutrition and Flavour Of Prepared Foodsmentioning
confidence: 99%